Mathematical challenges in the theory of chemotaxis - Biler, Piotr (Annales Mathematicae Silesianae, 2018)
We consider the simplest parabolic-elliptic model of chemotaxis in the whole space and in several space dimensions. Criteria either for the existence of radial global-in-time solutions or their blowup in terms of suitable Morrey spaces norms are discussed. This is an extended version of the lecture presented at the University of Silesia on January 12, 2018, commemorating Professor Andrzej Lasota - great scholar, master of fine mathematics and applications to real world.